Training clinical professionals to deliver a patient centered intervention in healthcare settings - Monica M. Matthieu; Ciara M. Oliver; Jane Ann McCullough; Mary J. Mallory; Laura D. Taylor; Jennifer A. Koget; Jamie Jensen; David A. Adkins; Robin M. Smith; Kimberly K. Garner (BMC Medical Education)
Abstract Within the healthcare settings of the United States Department of Veterans Affairs (VA), one patient-centered intervention, Advance Care Planning via Group Visits (ACP-GV), engages veterans and those they trust in advance care planning (ACP) by facilitating a discussion that encourages participants to plan for future healthcare needs. ACP-GV is a one-hour, single session group intervention facilitated by a trained clinical professional (e.g., physician, nurse, social worker, psychologist, chaplain) and delivered in a healthcare or community-based setting. Using reporting guidelines for group-based and educational interventions, this paper aims to describe the ACP-GV Facilitator Training used to prepare clinical professionals to offer the ACP-GV intervention to participants. We provide health professional students and early career health professionals with an overview of the training and key tips for using group modalities in the clinical setting. Although the training is initially directed towards health professionals who are learning to offer ACP-GV for the first time, our tips for teaching also focus on and extend to facilitating ACP-GV directly with veterans, caregivers, and those they trust. The ACP-GV Facilitator Training is sequential in that it expects clinicians to first learn the required educational content and how to plan a group, then it engages clinicians in practicing group facilitation skills. At the conclusion of the training, clinicians are then instructed to use the training materials to transfer the information and skills they learned about ACP-GV to patients they encounter in their respective work settings. The culmination of the ACP-GV Facilitator Training is, therefore, when the clinician is able to facilitate their own group, guide discussions and activities, actively use training materials, and encourage veterans and those they trust to participate in a discussion regarding ACP in a group setting. Finally, we share key resources for publicly available and accessible online trainings to promote spread outside of VA. ACP-GV’s Facilitator Training can assist healthcare professionals in implementing ACP-GV in a variety of care settings.